Editor's Note (Nigerian Journal of Technology, 2020)
Dear Readers,In this issue, some support staff had to come back to work; in the last issue they all had to work from home. We are again glad to publish the July 2020 issue online. Our issue statistics are shown in Table 1.The COVID-19 allowed many authors time to complete and submit their articles. So in this issue, we have 38 articles instead our normal 35. Some outstanding articles has been pre-scheduled for October 2020.